2012
DOI: 10.1093/mp/sss033
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Changes in Microtubule Distribution Correlate with Guard Cell Function in Arabidopsis

Abstract: Radially arranged cortical microtubules are a prominent feature of guard cells. We observed guard cells expressing GFP-tubulin (GFP-TUA6) with confocal microscopy and found recognizable changes in the appearance of microtubules when stomata open or close (Eisinger et al., 2012). In the present study, analysis of fluorescence distribution showed a dramatic increase in peak intensities of microtubule bundles within guard cells as stomata open. This increase was correlated with an increase in the total fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 24 publications
0
38
1
1
Order By: Relevance
“…The degree of colocalization in guard cells was not as high as that reported previously in dark-grown hypocotyls (Paredez et al, 2006;Li et al, 2012), suggesting that the behavior of CSCs is cell type specific. Previous research in guard cells expressing GFP-tagged tubulin revealed a decrease in cortical MTs upon stomatal closure (Eisinger et al, 2012a(Eisinger et al, , 2012b. However, our quantifications of mCherry-TUA5-labeled MT fluorescence area and intensity in guard cells did not show any significant differences between open and closed stomata (Supplemental Table S1), ruling out the possibility that the reduced degree of CSC-MT colocalization we observed upon stomatal closure is due to fewer MTs for CSCs to move along.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…The degree of colocalization in guard cells was not as high as that reported previously in dark-grown hypocotyls (Paredez et al, 2006;Li et al, 2012), suggesting that the behavior of CSCs is cell type specific. Previous research in guard cells expressing GFP-tagged tubulin revealed a decrease in cortical MTs upon stomatal closure (Eisinger et al, 2012a(Eisinger et al, , 2012b. However, our quantifications of mCherry-TUA5-labeled MT fluorescence area and intensity in guard cells did not show any significant differences between open and closed stomata (Supplemental Table S1), ruling out the possibility that the reduced degree of CSC-MT colocalization we observed upon stomatal closure is due to fewer MTs for CSCs to move along.…”
Section: Discussioncontrasting
confidence: 50%
“…Since CSCs move in alignment with cortical MTs (Paredez et al, 2006) and MT organization changes as stomata close in Arabidopsis guard cells (Eisinger et al, 2012a(Eisinger et al, , 2012b, we next asked whether CSCs might dissociate from underlying MTs and go off the rails during stomatal closure. We performed dual-channel spinning disk confocal imaging of CESAs and MTs in guard cells using Arabidopsis 6-d-old seedlings expressing GFP-CESA3, a marker for CSCs, and mCherry-TUA5, a marker for MTs (Gutierrez et al, 2009), which allowed us to analyze colocalization between CSCs and MTs in guard cells at different developmental stages and functional states.…”
Section: Colocalization Between Gfp-cesa3 Particles and Microtubules mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, although our study has well established that a linear intracellular signaling pathway including GPA1-dependent H 2 O 2 production and subsequent NO accumulation controls the low dose of UV-B-induced stomatal closure, the mechanism by which UV-Bdependent NO induces stomatal closure is still unclear. The structure and dynamics of cytoskeleton, the main cellular players in stomatal movement (Huang et al, 2009;Eisinger et al, 2012aEisinger et al, , 2012b) that can control ion channels in guard cells (Zhang et al, 2007), have been shown to be regulated by NO as well as H 2 O 2 (Huang et al, 2009;Wilkins et al, 2011;Yemets et al, 2011). Recent evidence also suggests that NO mediates UV-B signaling in plant cells by modulating cytoskeleton (Yemets et al, 2011;Krasylenko et al, 2012).…”
Section: Nia1-dependent No Mediates Uv-b-induced Stomatal Closurementioning
confidence: 99%
“…35 Microtubule arrays are required for normal guard cell function by changes in microtubule clustering or bundling, but the role of the microtubule cytoskeleton during stomatal movements is still controversial. 36 Jiang et al (2013) described PA induced stomatal closure by integrating calcium signal and microtubule arrays in response to ABA in Arabidopsis. Under ABA treatment, cytoplasmic calcium elevated and activated AtPLDα1 to produce PA. Then PA induced stomatal closure by microtubuledependent or independent pathway.…”
Section: Phospholipids Regulating Microtubular Arrays In Response To mentioning
confidence: 99%